Unmasking Logical Fallacies: An Analysis of The 2024 Indonesian Vice-Presidential Debates - Cholifah, Anjar Nur; Alfaruqy, Doni; Pustika, Reza; Sunarsih, Sunarsih (Journal of Pragmatics and Discourse Research, 2024)
The logical fallacies that emerged in the 2024 Indonesian vice-presidential candidate debates is interested. By analyzing debate through a descriptive qualitative approach and employing Damer's (2009) classification theory, the study evaluates the presence of unconvincing arguments in the discourse of the three vice-presidential candidates. Logical fallacies, which are errors in reasoning, can obscure listeners and impact comprehension and the quality of arguments in a debate. Data were collected by transcribing argumentative speeches from two YouTube videos of the debates. There were 120 utterances produced by the three vice-presidential candidates. From 120 utterances, 60 logical fallacies were found. The findings reveal that the most prevalent logical fallacies included red herrings (16.67%), where candidates diverted attention from relevant topics to irrelevant ones.  Ad hominem attacks (11.67%) were also common. Additionally, appeals to authority (11.67%) cited influential figures to support his argument on "ecological repentance," without strengthening the logical foundation of his argument. This research underscores the importance of recognizing cognitive biases that can undermine argument objectivity. The study highlights the need for heightened awareness of rhetorical manipulation among speakers and audiences to foster a more critical and informed debate culture. The study contributes to political communication studies by providing insights into the rhetorical strategies used in Indonesian political debates and their implications for democratic engagement. The prevalence of logical fallacies points to the necessity for improved debate standards to enhance rational political discourse, ultimately benefiting the democratic process by encouraging informed and constructive participation